Seasonal dynamics of sediment organic carbon storage for the upper streams of the Yangtze River - Hou, Jianfeng; Li, Fei; Wang, Zhihui; Li, Xuqing; Cao, Rui; Yang, Wanqin (Frontiers in Ecology and Evolution, 2023)
Forest streams reserve more than 90% of the organic carbon (OC) in sediments, thus playing crucial roles in the global carbon cycle. Although forest streams are widely distributed across various forest regions, seasonal dynamics of OC in forest sediments have not been fully investigated. Here, we sampled soils (0-5 cm) in 15 representative forest stream sediments for 5 critical periods (snowmelt season, early growing season, growing season, late growing season, and seasonal snow cover season) during a one-year investigation in a geologically fragile subalpine coniferous forest catchment in the upper reaches of the Yangtze River in Sichuan province and the OC concentrations were measured by potassium dichromate external heating method. The OC concentration of stream sediments ranged from 6.39 to 458.93 g kg-1, and the average was 84.56 g kg-1 for 15 streams in 5 critical periods during a 1-year investigation. Correspondingly, their stocks ranged from 2.05 to 310.56 kg m-2, and the average was 46.03 kg m-2. The maximum and minimum OC stocks were consistently observed during the late growing season and the snowmelt season, respectively. Otherwise, the OC stocks ranged from 1.31 to 218.05, 1.29 to 182.64, and 0.99 to 190.38 kg m-2 for the upstream, midstream, and downstream sediments, and the average was 39.36, 36.58, and 37.93 kg m-2, respectively. The average ratios of the OC stocks of the upstream and downstream ranged from 0.10-6.31, with an average of 1.43, during 5 critical periods, which indicated that the forest stream sediments may play crucial roles as carbon sources. Furthermore, based on regression analysis, we found that the seasonal dynamics of OC concentrations and stocks were mainly regulated by precipitation, temperature, sediment depth, and litter carbon input to the streams together. These findings demonstrate that forest stream sediments may play crucial roles in the carbon biogeochemical cycle of subalpine forests and adjoining streams.